Adenomyoepithelioma of breast - S Pradhan; RP Yadav (Association of Clinical Pathologists of Nepal, 2011)
Adenomyoepithelioma is rare tumors of the breast. It is a benign tumor with balanced proliferation of both epithelial and myoepithelial cells. This benign tumor is known for its recurrences and metastatic potential. Hence accurate diagnosis with close follow up is mandatory. We present a case report on a young lady with adenomyoepithelioma who presented with well defined small nodules in her right breast. Keywords: Adenomyoepithelioma; Myoepithelial cells DOI: http://dx.doi.org/10.3126/jpn.v1i2.5412 JPN 2011; 1(2): 154-157